Preparasi Jaringan dan Identifikasi Kerusakan Hati Tikus Yang Diinduksi Fenilhidrazin (PHZ) - M. Reyza Akbar; Ema Marminto; Manasalwah Alina Putri; Fitra Wahyuni; Anggit Prima Nugraha; Anggari Linda Destiana; Ade Adriadi (JOURNAL SAINS STUDENT RESEARCH, 2026)
Phenylhydrazine (PHZ) is a chemical compound that can induce hemolytic anemia and oxidative stress in experimental animals. This study aims to perform liver tissue preparation and identify histopathological changes caused by PHZ induction. White rats (Rattus norvegicus) were divided into two groups: the control group given 0.9% saline and the treatment group induced with PHZ at a dose of 60 mg/kg body weight intraperitoneally for three consecutive days. Tissue preparation included fixation using 10% formalin, dehydration with graded alcohol (70%, 80%, 90%, and 100%), clearing using xylene, embedding in paraffin, tissue sectioning at 4-5 μm thickness with a microtome, and Hematoxylin-Eosin (HE) staining. The results showed that PHZ induction caused a significant decrease in hemoglobin levels from 17-21 g/dL to 9.5-11.3 g/dL. Histological observation of liver tissue in PHZ-induced rats showed hepatocyte degeneration, cytoplasmic vacuolization, sinusoidal congestion, inflammatory cell infiltration, and cell necrosis. Spleen tissue showed red pulp hyperplasia and increased phagocytic activity. The tissue preparation successfully produced good histological preparations and allowed clear identification of histopathological changes. It can be concluded that phenylhydrazine is hepatotoxic and causes liver tissue damage through oxidative stress mechanisms.